Effect of different process parameters on the heat transfer of liquid coolant in electronic system / \c Wan Mohd Arif Wan Ibrahim. - Wan Mohd Arif Wan Ibrahim (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
Experiments are conducted to determine the effect of mass flow rate and different input power to the cooling performance of different liquid cooling inclusive of alumina sol, vegetable oil and water on indirect liquid cooling system of a computer ; to study the effect of different liquid cooling materials on the performance of a liquid cooling system ; to determine the effects of different pH and concentration on the stabilityof alumina sol ; to optimise the process parameters of a liquid cooling materials.